Ensuring Optimal Productivity: Linking Incentives, Safety Culture, and Output in the Food and Beverage Industry - Denia Amastuti; Rima Rahmayanti (Al-Qalam Institue, 2025)
This study explores the impact of rewards and work discipline on employee productivity, a leading food and beverage manufacturing company. The research aims to analyse how rewards influence productivity, with work discipline acting as a mediator. A quantitative, causal design was employed, using questionnaires, interviews, and observations to collect data from 100 respondents. The findings indicate that rewards, particularly performance-based incentives and bonuses, positively affect work discipline, thereby enhancing productivity. However, base salary adjustments and bonus transparency were found to be suboptimal. Work discipline, especially in areas such as safety compliance and task completion, plays a crucial mediating role in translating rewards into higher productivity. The study recommends restructuring reward systems to prioritise performance-based incentives while reinforcing discipline in critical areas. The research contributes to a deeper understanding of how rewards and discipline interact to improve manufacturing productivity, providing actionable insights for HR management in similar industries.